Target Therapy in Systemic Lupus Erythematosus: A Narrative Literature Review - Muhamad Delfin; Raveinal; Dwitya Elvira (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by the presence of autoantibodies against cells and involves many organ systems in the body. The Lupus Foundation of America estimates that around 1.5 million cases occur in America and at least 5 million cases occur worldwide. Every year it is estimated that there are around 16 thousand new cases of SLE. Various pro- and anti-inflammatory cytokines such as transforming growth factor (TGF), interleukin-10, B cell activating factor (BAFF), interferon-α, interleukin-17, and interleukin-23 play an important pathogenic role. Disruption of apoptotic cells and immune complexes is an important contributor to the development of this disease. Loss of immune tolerance increases antigenic load, excessive role of T cells, impaired B cell suppression and impaired transition of the immune response from T helper 1 (Th1) to Th2 which causes hyperactivity of B cells and produces pathogenic autoantibodies. The management of cases of severe or refractory SLE to conventional therapy has attracted a lot of attention in recent years, so that many researchers have developed several targeted therapies that have been tested on SLE, such as anti-CD 20 and CD 22 antibodies and BAFF inhibitors found in B lymphocyte cells. The Rituximab anti-CD 20 antibody target has been clinically proven to be able to improve the severity of SLE, while the effectiveness of other targeted therapies is still under research.